A new method for publishing three-dimensional content - Raush, E; Totrov, M; Marsden, B; Abagyan, R (Public Library of Science, 2009)
A new method for electronic publishing of articles with text linked to its interactive three dimensional content is described. The method is based on a single document containing a variety of objects such as formatted text, multiple three dimensional molecular objects, textured shapes and surfaces, data tables and graphs, chemical spreadsheets, alignments, etc. The 3D article can then be published for an online web delivery using the activeICM/active X components as well as be downloaded as a single file to be browsed with all its attached objects locally with the ICM browser. Both activeICM and ICM browser are freely available for the public. This method eliminates the need for multiple methods for the web and the local off-line delivery; it offers the dramatically enhanced, customizable and interactive delivery of article's three dimensional content and data attachments in a single compact file.